2000
DOI: 10.1097/00005053-200012000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Mood, and Functional Evaluations Using Touchscreen Technology

Abstract: We describe the design and development of the Cognitive Evaluation Protocol (CEP), a computer software program for evaluating cognitive and functional capacities and mood. The program is self-administered by subjects using touchscreen monitors for input. Stimuli in CEP subtests are randomized to reduce the effects of learning on repeated assessments. Findings demonstrate that a) minimum instruction is required for touchscreen use, even for computer-naive subjects; c) both normative subjects and psychiatric pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…1 Using a self-completed computerized questionnaire, patients can report completion of preventive health services as well as pain and health status. 2,3 Computer algorithms can score and present information from validated questionnaires such as the RAND-36 or Center for Epidemiologic Studies Depression Scale in real time, enabling use during routine patient encounters. Physicians can then respond to issues identified while saving time on data collection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Using a self-completed computerized questionnaire, patients can report completion of preventive health services as well as pain and health status. 2,3 Computer algorithms can score and present information from validated questionnaires such as the RAND-36 or Center for Epidemiologic Studies Depression Scale in real time, enabling use during routine patient encounters. Physicians can then respond to issues identified while saving time on data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians can then respond to issues identified while saving time on data collection. 3,4 Computerized questionnaires can also employ skip patterns, obviating the need for patients to answer redundant questions while also ensuring that all relevant questions are completed. Additionally, prior research has found that information collected via computer is valid compared to paper and pencil surveys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All such devices will be referred to as touch screens in the following text. Touch screens convey a direct bond between displayed information and haptic interaction and thus are very intuitive and close to lowest level sensorimotor processes, which has manifested not only in human psychology research (for example (McGuire et al, 2000), (Weber et al, 2003) and others), but also in animal behaviour experiments (for example (Conway & Christiansen, 2001), (Hashiya & Kojima, 1997) and many others). The popularity of touch screens is also due to their hardware, software and functional compatibility with computer mice, which significantly simplifies their application to areas, where information technology with typical user interfaces is already being extensively used.…”
Section: Introductionmentioning
confidence: 99%